Occurrence of self reported hand eczema in Swedish bakers. Issue 11 (November 1998) - Brisman, J; Meding, B; Järvholm, B
Abstract : OBJECTIVES: To estimate the risk of bakers developing hand eczema. The importance of atopy was studied as well as change of job due to hand eczema. METHODS: A retrospective cohort study was performed among bakers trained in Swedish trade schools in 1961-89 (n = 2923). School referents followed other programmes (n = 1258); population controls were randomly selected from the general population (n = 1258). A questionnaire on self reported hand eczema, year of onset of hand eczema, change of work due to hand eczema, childhood eczema, family atopy, and work history was posted to all participants. RESULTS: The incidence of hand eczema among male controls was 4.4-5.4 cases/1, 000 person-years compared with 16.7 for bakery work. The corresponding figures for women were 11.3-14.1 compared with 34.4. The relative risk for male bakers was 3.5 (95% confidence interval (95% CI) 2.8 to 4.5) and for female bakers 2.8 (2.2 to 3.6). Skin atopy increased the incidence about threefold and a synergistic effect of atopy and exposure was indicated. Also, bakers had changed job significantly more often than controls. CONCLUSIONS: Swedish bakers, mainly working during the 1970s and 1980s, have about a threefold increased risk of hand eczema. There seems to be a synergistic effect of atopy and occupational exposure.